2023
DOI: 10.1155/2023/3308651
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Abundance, and Distribution of Avifauna in District Jhang, Pakistan

Ahmad Zaman,
Azhar Rafique,
Asma Ashraf
et al.

Abstract: The present study was conducted from March 2021 to February 2022 in the Thal desert and Trimmu barrage of district Jhang located in the Punjab province of Pakistan to find out the diversity, abundance, and distribution of birds. The point count method was used for the Trimmu barrage, and the line transect method was used for the collection of data in the Thal desert area. We recorded 31,696 individuals belonging to 67 species of birds from two distinct types of habitats (Thal desert and Trimmu barrage) of dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The barrage area encompasses a diverse range of aquatic and terrestrial ecosystems, making it a highly suitable habitat for a wide array of migratory and endemic avian species [6]. Zaman et al [7] observed fifty-eight species of resident and migratory birds at Trimmu barrage. Taunsa barrage and Chashma barrage serve as the significant wetland habitats for both international and local migratory bird species.…”
Section: Introductionmentioning
confidence: 99%
“…The barrage area encompasses a diverse range of aquatic and terrestrial ecosystems, making it a highly suitable habitat for a wide array of migratory and endemic avian species [6]. Zaman et al [7] observed fifty-eight species of resident and migratory birds at Trimmu barrage. Taunsa barrage and Chashma barrage serve as the significant wetland habitats for both international and local migratory bird species.…”
Section: Introductionmentioning
confidence: 99%